Agarwood plantation at BRAC tea estate: introduction, environmental factors and financial analysis - Akter, Nasima; Neelim, Ananta Z (BRAC, 2019)
The Aquillaria malaccensis (known as agar) produces agarwood which is used in perfumes, incense and medicines, and thus, can be extremely valuable. Excessive harvesting of agarwood has made this species threatened. Considering its conservation value and economic benefit BRAC has started agarwood plantation at Kaiyachara Tea Estate from July. 2007. At Kaiychara tea estate, a plantation of about 17 acres has been created, where 83,400 agar seedlings have been planted between August and October 2007. In addition, 700,000 agar seedlings have been planted in two nurseries, namely 'Kaiya' and 'Sirgasia', at Kaiyachara tea estate. The survival rate of young seedlings was around 95%, which can be considered impressive. The habitat provided by the environment in the tea estate, along with the microclimatic and soil condition in that area is favourable for growing agar plants. Initially, the BRAC tea estate plans to plant 50 acres of land with agar plant, after which agarwood harvesting would take place after 12 years. Assuming 90% survival rate and 2 kg premium quality agarwood production per plant the estimated investment related to plantation would be Tk. 145,497,198 and total return would be Tk. 60,907,155,348 with the rate of return 41.861%. However, this high rate of return is an underestimate given the environmental benefits of this plantation would generate. The establishment of this plantation would also be significant in terms of the environmental conservation of this endangered species, as well as provide a carbon sink to reduce green house gases. Furthermore, there are potential opportunities that would arise in the future for improving the livelihoods of poor people in the region by providing income generating means. This report was prepared after field investigation and laboratory analysis and contains suggestions regarding proper management of the plantation as well as further research.